Hungary : First Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2011)
The economic development of Hungary after the economic crisis is discussed. Hungary's economic program supported by Stand-By Arrangement has been successful in strengthening the economy and stabilizing market conditions. Given Hungary's high public debt and large financing needs, Executive Directors emphasized the need for full and timely implementation of consolidation measures. Directors also recognized the positive collaboration between the European Union and the IMF during the program period. Furthermore, the foreclosure moratorium continues to prevent banks from cleaning balance sheets.